Gender Differences in Emotional Maturity: A Comparative Analysis of Male and Female Populations - Dr. Mandeep Kaur (Innovative Research Thoughts, 2024)
This study examines how emotional maturity varies by gender among a sample of 200 people, 100 males and 100 females. A key psychological concept linked to a person's capacity for efficient emotion regulation is emotional maturity. The emotional maturity of males and girls was investigated using mean scores, standard deviations (SD), standard error of the difference (SED), and t-values. The results show that, on average, males showed higher emotional maturity than females, with a mean score of 126.76 (SD = 21.07) compared to 120.89 (SD = 17.52). There was a statistically significant difference in the emotional maturity scores between boys and girls, as shown by the standard error of the difference (SED), which was estimated as 2.74, and the t-value for the comparison between the two groups, which was 2.14. These findings shed important new light on the gender-based differences in emotional maturity and emphasise the need for more investigation into the underlying causes of these discrepancies. In light of these findings, implications for mental health and emotional wellbeing are considered.